Karakteristik Pendaratan Penyu Hijau (Chelonia mydas, Linnaeus 1758) di Pesisir Pantai Tanjung Kemuning Tanjung Api Dan Pantai Belacan Kecamatan Paloh Kabupaten Sambas - Ari Hepi Yanti, Maulidil Anshary, Tri Rima Setyawati (Universitas Tanjungpura, 2014)
The frequency of green turtle (Chelonia mydas) landing is largely determined by the environmental conditions and human activities in a coastal area. This research aims to determine the frequency of landings, the number ofC. mydas at every landing time and the landing periods ofthehighest frequency ofC. mydas occurring in Tanjung Kemuning beach, Tanjung Api beach, and Belacan beach. The research was conducted by using direct observation in the field. The surveyrevealed that the frequency of C. mydas in beach landings in Belacan beach, Tanjung Kemuning beach, and Tanjung Api beach during the period from July to September 2013, is between 35.88% and 100 %. The numbers ofC. mydaslanded inBelacan beach, Tanjung Kemuning beach, and Tanjung Api beach are 20 - 28 individuals, 144-235 individuals and 107-183 individuals res pectively. Landing highest reached at 19:00 pm - 22:00 pm and 23:00 pm - 2:00 am. The environmental conditions in Tanjung Kemuning beach, Tanjung Api beach, and Belacan beach is able to support the landing activities of C. mydas.